Effects of inclination and rotation on the convective heat transfer characterstics of discrete heat sources - Jin, Linfang (2008)
The dissertation presents a three-dimensional (3-D) steady computational model and a two-dimensional (2-D) unsteady model using developed programs, together with experimental studies, to investigate effects of inclination and rotation on natural convection characteristic from an array of discrete heat sources in a closed enclosure. Effects of inclination on natural convection in a rectangular cavity with a 3x3 array of discrete heaters on one wall are presented firstly. Generally, the heaters in the same row have almost the same temperature in the experiments, due to weak velocity in the horizontal direction. In-depth 2-D and 3-D numerical simulations for laminar flow are implemented and validated by experimental results.